MANAJEMEN PROGRAM TAHFIDZ DALAM MEWUJUDKAN GENERASI PENGHAFAL QURAN DI SMP SWASTA LAMPUNG UTARA - Erli Yanty Rihana Paramida; Romlah; Septuri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The current generation faces significant challenges in terms of interest in memorizing the Qur'an. Factors such as high academic pressure, the influence of social media, and a busy lifestyle contribute to low motivation in memorizing. In addition, the lack of encouragement and minimal understanding of the importance of studying and memorizing the Qur'an are the main causes of the weak enthusiasm of the younger generation for tahfidz activities. This study aims to analyze the management of the Quran Tahfidz program at SMP Ibnu Rusyd and SMP Tahfidz Quran Nurul Muttaqin through four indicators of educational management, namely: planning, organizing, implementing, and supervising. The approach used is qualitative with data collection techniques in the form of interviews, observations, and documentation. The results of the study show that although the two schools have different approaches in implementing the tahfidz program, both have succeeded in forming the character of students based on the values ​​of the Qur'an. SMP Ibnu Rusyd applies an inclusive and open gradual coaching model, while SMP Tahfidz Quran Nurul Muttaqin carries a selective system with intensive tahsin and daily halaqah. The new findings of this study include an inclusive model based on Islamic boarding schools in public schools, a spiritual-based teacher evaluation forum (Ngopi Dhuha), and the use of colorful memorization mushafs structured in halaqah. This study provides an important contribution to the development of the management of the Tahfidz Quran program in formal educational institutions, especially in responding to the challenges of today's generation regarding the interest in memorizing the Al-Qur'an.